2019
DOI: 10.15517/revedu.v43i2.30564
|View full text |Cite
|
Sign up to set email alerts
|

El rendimiento escolar y el uso de videojuegos en estudiantes de básica secundaria del municipio de La Estrella- Antioquia

Abstract: El presente artículo expone los resultados obtenidos en la investigación desarrollada en el año 2015 sobre la relación existente entre el uso de videojuegos y el rendimiento académico de estudiantes de básica secundaria, entre los 12 y 14 años de edad, de cuatro colegios del municipio de la Estrella en Antioquia. La Metodología empleada para este estudio fue un enfoque empírico analítico, descriptivo correlacional, la muestra estuvo compuesta por 335 estudiantes a quienes se les aplicó el cuestionario de uso p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…Answering the other question raised, referring to whether the explanation of the usefulness of video games in the learning process affects sociodemographic elements, we stop our attention to gender, it has been observed that there are no differences between both genders in terms of the usefulness they perceive in video games regarding the learning of secondary content in a different way [42,43]. However, while men determine the suitability seen in video games before culture in the educational success (AOVCEE) and to diversity (AOVD), women do in fitness observed in video games to the culture in the educational success process (AOVCEE), hours playing the weekend (HJVFS), and before diversity (AOVD).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Answering the other question raised, referring to whether the explanation of the usefulness of video games in the learning process affects sociodemographic elements, we stop our attention to gender, it has been observed that there are no differences between both genders in terms of the usefulness they perceive in video games regarding the learning of secondary content in a different way [42,43]. However, while men determine the suitability seen in video games before culture in the educational success (AOVCEE) and to diversity (AOVD), women do in fitness observed in video games to the culture in the educational success process (AOVCEE), hours playing the weekend (HJVFS), and before diversity (AOVD).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, in terms of these aspects, under the prism of perception of the students of secondary education, which explain the usefulness of the game in the process of learning, it doesn't go against the studies already carried out [4,10], where it is able to manifest the attribution that will give to these resources for their progress in the learning process [15,42]. In the same way, the usefulness of the games in this acquired knowledge of content, becomes the keys to unfold as active and efficient citizens of the XXI century, impinges on the job that made of the same, an aspect to consider when promoting political education to address the addictions and issues of use of these resources [21].…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados no coinciden con los hallados en otras investigaciones (Dindar, 2018;Restrepo-Escobar et al, 2019), donde se señala que los videojuegos no puedan llegar a ser la causa de los problemas académicos de escolares en la etapa escolar (Celis & Escobar, 2012). En aproximadamente 219.000 estudiantes, se ha hallado que la frecuencia de los videojuegos no parece tener una relación sistemática con el rendimiento académico.…”
Section: Discusión Y Conclusionesunclassified
“…En este sentido, en lo que se refiere a las modalidades de videojuegos, los menos utilizados son los juegos educativos y de agilidad mental, existiendo una clara inclinación de los colegios públicos a jugar todo tipo de videojuegos (Restrepo-Escobar et al, 2019). En esta línea argumental, el uso de videojuegos educativos parece relacionarse con una mayor satisfacción social, apoyo de pares y comportamiento prosocial, lo que lleva a un mayor bienestar, mientras que los videojuegos violentos se relacionan con un mayor acoso escolar y una menor satisfacción social y prosocialidad (Shoshani et al, 2021).…”
Section: Discusión Y Conclusionesunclassified
“…En el estudio de Cano-Mañas (2017) se realizaron sesiones a lo largo de un total de 8 semanas. Y en el estudio de Fernandes (2017) se realizaron un total de 10 sesiones, dos veces por semana durante 1 mes.Este estudio comparte la idea de que los videojuegos pueden ser utilizados como método de intervención(Cano-Mañas et al, 2017;Fernandes et al, 2017;Zolyomi & Schmalz, 2017) y como herramienta fundamental para el desarrollo de habilidades(de Prado, 2018;Restrepo Escobar, Taborda, Magdaly, & Arboleda Sierra, 2019).…”
unclassified